MOSIX: Implementation, trend and benchmark in Malaysia - Hakim M.; Jais J.; Salwa S. (2023)
This paper is part of a larger project on MOSIX cluster computing. This paper also is a continuation of the previously published paper regarding MOSIX potential performance and threat [9]. The main focuses are on MOSIX implementation, survey and benchmark on MOSIX performance. In this paper, the information is presented in a broad to narrow approach, which is from an overview of shared network and all the way to the MOSIX. We also test several testing algorithm to benchmark the performance of MOSIX in order to find out the real potential of MOSIX distributed operating system. 2008 IEEE.